Characteristics of PM2.5-bound secondary organic aerosol tracers in a coastal city in Southeastern China: Seasonal patterns and pollution identification. (15th September 2020) - Liu, Taotao; Hu, Baoye; Xu, Xinbei; Hong, Youwei; Zhang, Yanru; Wu, Xin; Xu, Lingling; Li, Mengren; Chen, Yanting; Chen, Xiaoqiu; Chen, Jinsheng
Abstract: Secondary organic aerosol (SOA) plays an important role in global climate change and air quality, and SOA tracers most directly characterize the sources and formation mechanisms of SOA. Four seasons of observation of SOA tracers was carried out in a coastal city of southeastern China. Fourteen PM2.5 -bound SOA tracers, including isoprene (SOAI ), α/β-pinene (SOAM ), β-caryophyllene (SOAC ), and toluene (SOAA ), were measured using the GC–MS method. The concentrations of SOA tracers in Fuzhou were 25.9 ± 19.9 ng m −3 (SOAM ), 7.45 ± 8.53 ng m −3 (SOAI ), 3.15 ± 1.99 ng m −3 (SOAC ), and 2.63 ± 1.54 ng m −3 (SOAA ). The elevated SOAI concentration in summer was mainly controlled by high biogenic isoprene emission and strong oxidation, and biomass burning contributed strongly to DHOPA (SOAA ) in fall. SO4 2− and H + insitu had an increased impact on later-generation SOAI products and low-NOx SOAM products. Based on the ratio of MGA/MTLs and MBTCA/(PA + PNA), atmospheric oxidation capacity (Ox, =NO2 +O3 ) had a significant impact on the aerosol aging of SOA tracers. The increased proportions of low-NOx SOAI products were 3.23–7.21 times higher than those of high-NOx products from non-haze to haze periods, suggesting the influence of high SO4 2− concentration and RH on the reaction channel for SOAI formation. The percentages of later-generation SOAM products during RT were 2.46 times higher than those of first-generation products, suggesting the influence of aerosol aging during the regional transport. Both continental Asian outflow and biomass-burning plumes promoted precursor emissions and the formation process of SOA during the haze pollution events. These related findings help to understand the occurrence, sources and formation of SOA in coastal areas. Highlights: SO4 2− and H + insitu had an increased impact on low-NOx SOAI products and later-generation SOAM products. The HO2 channel was the main chemical reaction of SOA during haze periods. Biomass-burning plumes promoted precursor emissions and the formation of SOA during haze events with regional transport.